2001
DOI: 10.1177/153537020222600711
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelial Wound Healing

Abstract: One of the Important functions of the cornea Is to maintain normal vision by refracting light onto the lens and retina. This property is dependent In part on the ability of the corneal epithelium to undergo continuous renewal. Epithelial renewal is essential because It enables this tissue to act as a barrier that protects the corneal Interior from becoming infected by noxious environmental agents. Furthermore, the smooth optical properties of the corneal epithelial surface are sustained through this renewal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
215
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(228 citation statements)
references
References 123 publications
3
215
0
10
Order By: Relevance
“…However, there is currently very little information regarding how UV irradiation induces corneal epithelial cell apoptosis (Lu et al, 2001b). Recent studies provide cellular and molecular mechanisms involving hyperactivation of a K + channel in corneal epithelial cells Wang et al, 2003).…”
Section: Uv Irradiation-induced K + Channel Hyperactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is currently very little information regarding how UV irradiation induces corneal epithelial cell apoptosis (Lu et al, 2001b). Recent studies provide cellular and molecular mechanisms involving hyperactivation of a K + channel in corneal epithelial cells Wang et al, 2003).…”
Section: Uv Irradiation-induced K + Channel Hyperactivitymentioning
confidence: 99%
“…For example, we, as well as other researchers, have shown that stimulation of K + channel activity and dramatic loss of intracellular K + can result in apoptosis in the corneal epithelium, neurons, myeloblastic ML-1 cells, and other cell types (Schulz et al, 1996;Eldadah et al, 1997;Yu et al, 1997;Wang et al, 1999aWang et al, ,2003Lu et al, 2003;Trimarchi et al, 2002;Remillard and Yuan, 2004). It seems that there are dual functions of K + channels involving cell proliferation regulated by epidermal growth factor (EGF) (Lu et al, 2001a) and playing a role in mediating cell death induced by UV irradiation (Wang et al, 1999aLu et al, 2003). We found in corneal epithelial cells that K + channel activity is required for growth factor-stimulated activation of extracellularregulated kinase (ERK) (a MAP kinase) limb and proliferation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When wounding occurs, the cornea sets into action various mechanisms to repair the injured area with the aim to maintain and/or restore optimum optical properties (Jester et al, 1999a). After wounding, epithelial cells migrate and proliferate to replace damaged cells (Lu et al, 2001). As a consequence of wounding of the epithelium and/or the stroma, the underlying anterior stromal cells undergo apoptosis, while corneal stromal cells distal from the wound undergo phenotypic changes to fibroblasts and myofibroblasts (Jester et al, 1987;Jester et al, 1996;Jester et al, 1999b;Maltseva et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The corneal epithelial layer protects the eye structures behind it from environmental insults and infections to maintain the intact function of the vision system (1). Corneal epithelial cells undergo a self-renewal process to replace the surface layer cells and repair corneal surface wounds dependent on the stimulation of growth factors.…”
mentioning
confidence: 99%